D-dimer Level Variation in Hospitalized COVID-19 Patients - Aso Hemn Omar; Aras Othman Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The Coronavirus Disease 2019 (COVID-19) pandemic has posed significant challenges to global health systems. This study investigates the intricate relationship between COVID-19 infection and D-dimer levels in hospitalized cases. This research aims to decipher the role of D-dimer in COVID-19 severity and outcomes. Consequently, this study endeavors to evaluate the role of D-dimer in COVID-19 severity by analyzing patient data. The study's methodology entails a retrospective analysis of 300 COVID-19 patients admitted to a specialized hospital in Erbil, Iraq. Laboratory confirmation of COVID-19 was conducted using real-time reverse-transcriptase–polymerase-chain-reaction (RT-PCR) and rapid tests. D-dimer levels were measured using an enzyme-linked fluorescence test (ELFA) kit. The results of the study underscore the complex interplay between COVID-19 infection, D-dimer levels, age, and gender. Infections correlated with higher D-dimer levels, reflecting a significant impact of the virus on coagulation pathways. Notably, age and gender demonstrated influential roles in infection rates and D-dimer elevation. Older individuals exhibited higher infection rates, while males experienced greater D-dimer elevation. In conclusion, this research elucidates the relationship between COVID-19 infection, D-dimer levels, and patient outcomes, the study found that the infection spread between men more than women. As well as, elevated D-dimer levels emerge as a significant factor in disease progression, potentially influencing coagulation dysfunction and inflammatory responses. The study emphasizes the importance of comprehensive risk assessment and management strategies for severe COVID-19 cases.